A Comparison of the Adaptive Response of Staphylococcus aureus vs. Streptococcus mutans and the Development of Chlorhexidine Resistance - van de Lagemaat, Marieke; Stockbroekx, Valerie; Geertsema-Doornbusch, Gésinda I.; Dijk, Melissa; Carniello, Vera; Woudstra, Willem; van der Mei, Henny C.; Busscher, Henk J.; Ren, Yijin (Frontiers in Microbiology, 2022)
Antimicrobials with nonselective antibacterial efficacy such as chlorhexidine can be effective in reducing biofilm, but bear the risk of inducing resistance in specific bacteria. In clinical practice, bacteria such as Staphylococcus aureus have been found resistant to chlorhexidine, but other bacteria, including Streptococcus mutans, have largely remained susceptible to chlorhexidine despite its widespread use in oral healthcare. Here, we aim to forward a possible reason as to why S. aureus can acquire resistance against chlorhexidine, while S. mutans remains susceptible to chlorhexidine. Measurement of surface-enhanced fluorescence indicated that chlorhexidine caused gradual, but irreversible deformation to adhering green fluorescent S. aureus due to irreparable damage to the cell wall. Concurrently, the metabolic activity of adhering staphylococci was higher than of planktonic bacteria, suggesting efflux mechanisms may have been activated upon cell wall deformation, impeding the buildup of a high chlorhexidine concentration in the cytoplasm and therewith stimulating the development of chlorhexidine resistance in S. aureus. Exposure of S. mutans to chlorhexidine caused immediate, but reversible deformation in adhering streptococci, indicative of rapid self-repair of cell wall damage done by chlorhexidine. Due to cell wall self-repair, S. mutans will be unable to effectively reduce the chlorhexidine concentration in the cytoplasm causing solidification of the cytoplasm. In line, no increased metabolic activity was observed in S. mutans during exposure to chlorhexidine. Therewith, self-repair is suicidal and prevents the development of a chlorhexidine-resistant progeny in S. mutans.